Synthesis poly(hydroxamic acid) by modification of polyacrylamide hydrogels with hydroxylamine hydrochloride and application for adsorption of La(III), Pr(III) ions - Cong, Trinh Duc; Phuong, Hoang Thi; Thuc, Nguyen Thi; Manh, Nguyen Van; Khoi, Nguyen Van (Vietnam Journal of Chemistry, 2015)
Poly(hydroxamic acid) (PHA) was synthesised by modification of polyacrylamide hydrogels with hydroxylamine. Some effects such as temperature, time, hydroxylamine hydrochloride concentrations and pH on hydroxamic acid functional groups were studied. The results showed that hydroxamic acid functional groups in polymer is the highest in following conditions: 30 oC temperature; 24 hour, 3.3 M NH2OH.HCl concentrations and pH = 14. Beside, PHA was characterized by fourier transform infrared spectroscopy (FTIR) and scanning electron microscope (SEM). PHA were also applied for adsorption of La(III) and Pr(III) ions. The adsorption of La(III) and Pr(III) ions on poly(hydroxamic acid) conformed to linear form Langmuir adsorption isotherm, maximum capacities for La(III), Pr(III) were found as 234.19 and 209.64 mg/g at pH = 6, respectively. Keywords. Poly(hydroxamic acid), adsorption, ion-exchange, Praseodymium, Lanthanum.